Perjuangan Ken Arok Menjadi Raja Kerajaan Singosari Tahun 1222-1227 - Agus Susilo; Sarkowi Sarkowi (LP4MK STKIP PGRI Lubuklinggau, 2021)
One who has blue blood is identical to being a ruler. The highest satisfaction is when his desire is achieved perfectly. This has influenced Ken Arok who felt his desire should be realized as a king in the land of Java. After living in the wrong path by becoming a villain, until finally his meeting with a Brahmin whose Lohgawe made his life brighter.In writing this scientific work, the writer uses historical research methods. In historical research methods, many researchers use reference sources in the form of relevant journals and book sources that support in writing these scientific articles. The result of this discussion is that after going through the hard struggle of being a villain, being a person who was driven out of his residence, but luck continued to follow Ken Arok. His mission to become king, began by killing Tunggul Ametung with Mpu Gandring's Keris and married Ken Dedes. Subsequently defeated the Kingdom of Kediri and founded the Singosari Kingdom with the title Sri Rajasa Bhatara Sang Amurwabumi.